Philippine Halal Certification: Economic Viability and Structural Barriers - Martinez, Junna; Campos, Karl P. (Universitas Nahdlatul Ulama Surabaya, 2024)
As of this date, the global halal economy is significantly growing. The Philippines is one of those countries where the Muslim population is significantly increasing, which also resulted in a heightened demand for Halal-certified products and services in the industry. Halal certification is prominent because it undergoes a process where they certify products and services. This is also significant to non-Muslim consumers who embrace halal as one of their lifestyles. With this growing significance and potential economic viability, opportunities has opened for businesses to invest in halal certification. However, despite the significant growth, potential halal business owners still struggle from participating in this growing market due to the challenges they face, particularly in micro and small sector. A primary study found out the common barriers that are usually encountered and most of it are drawn from inconsistent interpretations by different certifying bodies. This study aims to address these challenges by offering recommendations to policymakers such as the halal-certifying bodies about the difficulties these businesses encounter. By addressing these challenges, the study seeks to help business owners recognize the competitive advantage of getting halal certification, given that not all are aware of its benefits. Furthermore, this study will help